Risk factors for developing COVID-19: a population-based longitudinal study (COVIDENCE UK). Issue 9 (30th November 2021) - Holt, Hayley; Talaei, Mohammad; Greenig, Matthew; Zenner, Dominik; Symons, Jane; Relton, Clare; Young, Katherine S; Davies, Molly R; Thompson, Katherine N; Ashman, Jed; Rajpoot, Sultan Saeed; Kayyale, Ahmed Ali; et al.
Abstract : Background: Risk factors for severe COVID-19 include older age, male sex, obesity, black or Asian ethnicity and underlying medical conditions. Whether these factors also influence susceptibility to developing COVID-19 is uncertain. Methods: We undertook a prospective, population-based cohort study (COVIDENCE UK) from 1 May 2020 to 5 February 2021. Baseline information on potential risk factors was captured by an online questionnaire. Monthly follow-up questionnaires captured incident COVID-19. We used logistic regression models to estimate multivariable-adjusted ORs (aORs) for associations between potential risk factors and odds of COVID-19. Results: We recorded 446 incident cases of COVID-19 in 15 227 participants (2.9%). Increased odds of developing COVID-19 were independently associated with Asian/Asian British versus white ethnicity (aOR 2.28, 95% CI 1.33 to 3.91), household overcrowding (aOR per additional 0.5 people/bedroom 1.26, 1.11 to 1.43), any versus no visits to/from other households in previous week (aOR 1.31, 1.06 to 1.62), number of visits to indoor public places (aOR per extra visit per week 1.05, 1.02 to 1.09), frontline occupation excluding health/social care versus no frontline occupation (aOR 1.49, 1.12 to 1.98) and raised body mass index (BMI) (aOR 1.50 (1.19 to 1.89) for BMI 25.0–30.0 kg/m 2 and 1.39 (1.06 to 1.84) for BMI >30.0 kg/m 2 versus BMI <25.0 kg/m 2 ). Atopic disease was independently associated with decreased odds (aOR 0.75, 0.59 to 0.97). No independent associations were seen for age, sex, other medical conditions, diet or micronutrient supplement use. Conclusions: After rigorous adjustment for factors influencing exposure to SARS-CoV-2, Asian/Asian British ethnicity and raised BMI were associated with increased odds of developing COVID-19, while atopic disease was associated with decreased odds. Trial registration number: ClinicalTrials.gov Registry (NCT04330599 ).